Role of Sales Promotion on Impulsive Buying Behavior of Skin Care Products - Mani, Ambica Prakash (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*307.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918543);" role="presentation">Sales promotions are important means of mobilizing sales on account of impulse buying. Skin care <span dir="ltr" style="left: calc(var(--scale-factor)*474.10px); top: calc(var(--scale-factor)*307.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891328);" role="presentation">products are <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959361);" role="presentation">typically associated with <span dir="ltr" style="left: calc(var(--scale-factor)*178.13px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962985);" role="presentation">longer life cycles and the loyalty generated among the users is also higher <span dir="ltr" style="left: calc(var(--scale-factor)*497.26px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950335);" role="presentation">due to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870318);" role="presentation">increased <span dir="ltr" style="left: calc(var(--scale-factor)*112.46px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907878);" role="presentation">span of usage. The present research initiative is an attempt to understand the effectiveness of different <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948458);" role="presentation">promotional techn<span dir="ltr" style="left: calc(var(--scale-factor)*147.14px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920254);" role="presentation">iques adopted <span dir="ltr" style="left: calc(var(--scale-factor)*209.69px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973659);" role="presentation">for skin care cosmetic products<span dir="ltr" style="left: calc(var(--scale-factor)*343.51px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966561);" role="presentation">. The findings are based on the responses <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935062);" role="presentation">collected from a sample of 250 respondent<span dir="ltr" style="left: calc(var(--scale-factor)*248.33px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970911);" role="presentation">s in Uttrakhand, India. M<span dir="ltr" style="left: calc(var(--scale-factor)*353.35px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945679);" role="presentation">ajority users are unmarried women in the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93136);" role="presentation">age group of 18-<span dir="ltr" style="left: calc(var(--scale-factor)*140.42px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933599);" role="presentation">25 years. Findings enabled to identify the <span dir="ltr" style="left: calc(var(--scale-factor)*313.51px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881158);" role="presentation">mos<span dir="ltr" style="left: calc(var(--scale-factor)*330.07px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922944);" role="presentation">t important reason <span dir="ltr" style="left: calc(var(--scale-factor)*407.47px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920139);" role="presentation">for use<span dir="ltr" style="left: calc(var(--scale-factor)*435.70px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92993);" role="presentation">, that <span dir="ltr" style="left: calc(var(--scale-factor)*459.58px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922732);" role="presentation">is <span dir="ltr" style="left: calc(var(--scale-factor)*469.42px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929029);" role="presentation">the desire for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971519);" role="presentation">fairer skin tone. The efficacy of different promotional techniques like discounts, free samples, trial options, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930896);" role="presentation">gifts, coupons, advertisements, celebrity endorsements, specialist advice is also studied. <span dir="ltr" style="left: calc(var(--scale-factor)*439.18px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.83266);" role="presentation">SP<span dir="ltr" style="left: calc(var(--scale-factor)*450.34px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.83266);" role="presentation">SS <span dir="ltr" style="left: calc(var(--scale-factor)*465.22px); top: calc(var(--scale-factor)*400.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971354);" role="presentation">22 is used for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*413.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890931);" role="presentation">analysing the data.